THE INFLUENCE OF WORK MOTIVATION ON OPERATIONAL EMPLOYEE PERFORMANCE AT PT. PUPUK INDONESIA LOGISTICS JAKARTA - Kakisina, Girnisia; Kwartama, Agung; Kurniadi, Bambang; Ariska, Riris; Ahmad, Syaiful (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2024)
To achieve this success, companies have production factors such as human resources, capital, raw materials and machines. However, compared to other company-specific factors, it is the human resource factor that makes the biggest or main contribution to the success of a company. Analyzing the coefficient of determination (Kd) obtained a coefficient of determination of 55.2%, which means work motivation (variable) is part of the author's analysis in the research. We analyzed the correlation coefficient (r) and found that the correlation coefficient r = 0.74. These results mean that the work incentives provided by a company are closely related to employee performance. If the correlation results are positive, it means the relationship is in the same direction, and when motivation decreases, employee performance also decreases. High work motivation encourages employees to work as best as possible according to the company's plans, thus supporting the company's survival.